Model kreativiti pengajaran guru bahasa arab di Malaysia - Mohammad Rusdi, Ab Majid; Che Mohd Zaid, Yusof; Mohd Alauddin, Othman; Aznida, Aziz (2021)
This study investigated the model of creativity of Arabic language teaching in Malaysia. Technological Pedagogical Content Knowledg (TPACK) has been made as the main model in this study. This model is based on a study which consisted of 530 Arabic language teachers from 7,309 teachers in Peninsular Malaysia including Sabah and Sarawak. Quantitative research methods were used and random sampling were carried out for the collection of data. The data were analyzed using the Statistical Package for Social Science (SPSS). The findings of this study explained that the model of teaching creativity needs to focus on Pedagogical Knowledge, Technological Pedagogical Content Knowledge, Pedagogical Content Knowledge and Technological Pedagogical Knowledge. In conclusion, the findings clearly indicate that the Arabic language teachers in Malaysia need to focus on the elements that have been stated to develop an excellent knowledge in creativity of teaching.